Incidence of Seed-borne Mycoflora on French Bean Mutants and its Antagonistic Activity against Trichoderma harzianum - Kakde, Swapnil E. Mahamune; Rajendra B. (Recent Research in Science and Technology, 2011)
Seed-borne mycoflora of two varieties of French bean viz. Waghya and Varun was studied. Seed mycoflora of nine mutants of Waghya and seven mutants of Varun was isolated on Glucose Nitrate Agar and Rose Bengal Agar Media. Thirteen fungi were isolated from Waghya variety and nine fungi were found to be associated with Varun variety. On both the varieties Macrophomina phaseolina showed its quantitative dominance which were followed by Aspergillus niger and Fusarium oxysporum. Broad pod mutant of variety Waghya showed maximum association of fungi while Long pod mutant showed minimum detection of fungi. Small leaf mutant of variety Varun was associated with maximum number of fungi while dwarf and branched mutant showed minimum detection of fungi. Waghya variety showed maximum incidence of fungi as compared to Varun variety. The antagonistic activity of Trichoderma harzianum against dominant fungi was also studied.